Acute Toxicity Test of Jatropha curcas L. on Nile Tilapia Seeds (Oreochromis niloticus L.) - Nurhidayanti Nurhidayanti (Science and Technology Indonesia, 2020)
ABSTRACT The study investigating acute toxicity test of Jatropha curcas L. on Nile tilapia seeds (Oreochromis niloticus L.), had been conducted in May 2017, in Balai Riset Perikanan dan Perairan Umum (BRPPU) Mariana, Banyuasin. This study was aimed to determine the concentration of Jatropha curcas seed powder needed to cause 50% death of Nile tilapia seeds (LT50). This acute toxicity test used biological test with exposure time of 96 hours. The concentrations of Jatropha curcas tested were 0 (control), 240, 288, 346, 415, 498, 597, and 716 ppm which were applied for 96 hours. Data were analyzed using Spearman-Karber method with SPSS. Result showed LC50 of 24 hours was 551,271 ppm, LC50 of 48 hours was 466,513 ppm, and LC50 of 96 hours was 393,892 ppm. Meanwhile, LT50 for 597 ppm of Jatropha curcas was 1285, 166 minutes, and LT50 for 761 ppm was 784,121 minutes. The higher the concentration of Jatropha curcas seeds given the fastest time needed to cause the death of Nile tilapia seeds, Jatropha curcas seeds had moderate toxicity. Keywords: Acute toxicity, Jatropha curcas L., Biological test, Oreochromis niloticus L